La erradicación de la apatridia en el Plan de Acción de Brasil - Mondelli, Juan Ignacio (2015)
The article comments the content of the chapter to eradicate statelessness of the Brazil Plan of Action, and its actions aimed at the prevention of statelessness, the protection of stateless persons, and the resolution of existing cases. It also explains the linkages of such actions with those contained in UNHCR Global Action Plan to End Statelessness. Finally, the article presents the current stage and some major developments in the region with regard to accession to the statelessness conventions, the adequacy of national legislation to international standards, the adoption of legal frameworks on the protection of stateless persons, the establishment of statelessness determination procedures, and the search of solutions to the problem of statelessness.